ANALISA SIFAT MEKANIS MATERIAL KOMPOSIT POLIMER BUSA DENGAN BLOWING AGENT SODIUM BICARBONAT DAN DIPERKUAT SERAT TANDAN KOSONG KELAPA SAWIT - Ade Irwan (Universitas Harapan Medan, 2019)
Empty palm fruit bunch fiber reinforced polymeric foam has been developing as alternative engineering material. This material uses unsaturated polyester resin (UPR) as its matrics, and treatmented empty palm fruit bunch fiber as its reinforcement element. Environmental friendly blowing agent has been used to get foamy structure in this material. This material tested to get properties of density, tension strength, static compression strength, and foams distribution. The result of this research is that A composition has the highest density for 665 kg/m3, with tension strength 0.05 MPa, compression strength 6.802 MPa and elastic modulus 37.859 Mpa. Eventhough additon of fiber could decrease mass of material, but in other side it could decrease the strenght of material too.